Welcome to Pathfinder - Ballantyne, Erin (Pathfinder: A Canadian Journal for Information Science Students and Early Career Professionals, 2020)
Some opening remarks on the publication of our first regular issue including brief explanation of our name and founding principles and listing of persons to whom thanks are most certainly due.